2021
DOI: 10.1177/09612033211040366
|View full text |Cite
|
Sign up to set email alerts
|

Association of MALAT-1 gene single nucleotide polymorphisms with genetic susceptibility to systemic lupus erythematosus

Abstract: Background: Abnormal expression and function of long non-coding RNAs (lncRNAs) are closely related to the pathogenesis of systemic lupus erythematosus (SLE). In this study, we aimed to investigate the association of lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT-1) gene single-nucleotide polymorphisms (SNPs) with susceptibility and clinical characteristics of SLE patients. Methods: A case-control study including 489 SLE patients and 492 healthy controls was conducted. Four MALAT-1 SNPs (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…On the other hand, MALAT1 is the key regulatory factor in the pathogenesis of SLE due to it exerting detrimental effects through the regulation of SIRT1 signaling [14]. The MALAT1 rs4102217 polymorphism is associated with susceptibility to SLE in humans [24]. The characteristics of CASC2 and MALAT1 suggest that they may affect the phenotype (i.e., histological class) of lupus nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, MALAT1 is the key regulatory factor in the pathogenesis of SLE due to it exerting detrimental effects through the regulation of SIRT1 signaling [14]. The MALAT1 rs4102217 polymorphism is associated with susceptibility to SLE in humans [24]. The characteristics of CASC2 and MALAT1 suggest that they may affect the phenotype (i.e., histological class) of lupus nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis‐associated lung adenocarcinoma transcript1 (MALAT‐1) is upregulated in several cancer cell types and promotes tumour growth and metastasis 60,61 . Mao et al found that MALAT‐1 gene polymorphisms rs4102217 locus was associated with the risk of SLE 62 . Although there are inconsistent findings regarding altered MALAT1 expression in SLE patients, a pathophysiological role for this lncRNA has been noted.…”
Section: Lncrnas In Peripheral Blood and Bone Marrow Samples From Slementioning
confidence: 99%
“…60,61 Mao et al found that MALAT-1 gene polymorphisms rs4102217 locus was associated with the risk of SLE. 62 Although there are inconsistent findings regarding altered MALAT1 expression in SLE patients, a pathophysiological role for this lncRNA has been noted. Yang et al demonstrated that MALAT-1 expression was aberrantly increased in PBMCs of SLE patients and predominantly expressed in human monocytes.…”
Section: Malat-1mentioning
confidence: 99%
“…MALAT1 has been demonstrated in cancers of breast, cervix, gallbladder, lung, ovary, pancreas, prostate, glioma, hepatocellular carcinoma and multiple myeloma [12]. There are also isolated studies on the role of long non-coding RNA Malat1 in the development of pathology of vessels, including lupus erythematosus [13], coronary artery disease [14] and the development of atherosclerosis, which is a predictor of stroke. It is reported that MALAT1 involved in the protection of cerebral microvessels after ischemic insult from a RNA sequencing study.…”
Section: Table 1 -Anthropometric Indicators In Persons Of Different S...mentioning
confidence: 99%